HP gaming - Isaacs, Andrew M.; Hedges, Leland (London : SAGE Publications Ltd, 2017)
This case study focuses on how a large company, Hewlett-Packard (HP) works through the strategic, branding, and organizational issues related to its new acquisition, VoodooPC. The case addresses some key issues related to acquisitions, especially how a large established company like HP navigates the sometimes complicated road of integrating a small, yet successful brand like VoodooPC.
Originally published in Isaacs, A., & Hedges, L. (2007). HP Gaming. The Berkeley-Haas Case Series. University of California, Berkeley. Haas School of Business.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Hewlett-Packard Company; Consolidation and merger of corporations -- Case studies; Business planning -- Case studies; Branding (Marketing) -- Case studies; Organizational behavior -- Case studies; Electronic apparatus and appliances -- Case studies